A new measure of the standard of living based on functionings - Wulf Gaertner; Yongsheng Xu (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2005)
Human development is about expanding the choices human beings have to lead lives that they value and is captured by its capability sets which consist of various functioning vectors. The standard of living is then reflected in capability sets. This paper proposes some particular ways of measuring the standard of living available either to an individual or a whole country, when the direction of the development of society represented by a reference functioning vector or a reference cone is uncertain. We provide axiomatic characterizations of the various measures proposed.
Keywords: C78; D63; D71; D74; O12; 330; functionings; capabilities; uncertainty; social progress; standard of living